Heavily Indebted Poor Countries (HIPC) Initiative and Multilateral Debt Relief Initiative (MDRI) : Statistical Update. (Policy Papers; Policy Paper ;, 2019)
This report reviews developments in the implementation of the Heavily Indebted Poor Countries (HIPC) Initiative and Multilateral Debt Relief Initiative (MDRI). It also provides updates on debt service and poverty-reducing expenditure by beneficiary countries, as well as on the cost of debt relief, creditor participation rates, and litigation against HIPCs.